South from America - Brenan Gerald (Penguin Books, 1963)
Preface, Arrival and Discovery, The Alpujarra, Friends and Neighbours, Lytton Strachey's Visit, Love Affairs and Politics, The Village Calendar, School and Church, The Fair at Ugijar, Masons and Animals, Beliefs and Rituals, The Lonely Scotsman, Food and the Phoenicians, Virginia Woolf's Visit, The High Mountains and Guadix, A Chapter of History, Almeria and Its Brothels, Almeria and Archaeology, Granada in the Twenties, Courtship and Marriage, Last Years at Yegen, A Postscript.
Preface, Arrival and Discovery, The Alpujarra, Friends and Neighbours, Lytton Strachey's Visit, Love Affairs and Politics, The Village Calendar, School and Church, The Fair at Ugijar, Masons and Animals, Beliefs and Rituals, The Lonely Scotsman, Food and the Phoenicians, Virginia Woolf's Visit, The High Mountains and Guadix, A Chapter of History, Almeria and Its Brothels, Almeria and Archaeology, Granada in the Twenties, Courtship and Marriage, Last Years at Yegen, A Postscript.